2023
DOI: 10.1302/0301-620x.105b9.bjj-2023-0780
|View full text |Cite
|
Sign up to set email alerts
|

Looking ahead to autumn

Fares S. Haddad

Abstract: Estimating incidence rates of periprosthetic joint infection after hip and knee arthroplasty for osteoarthritis using linked registry and administrative health data. Bone Joint J. 2022;104-B(9):1060-1066. 41. Ivy MI, Sharma K, Greenwood-Quaintance KE, et al. Synovial fluid α defensin has comparable accuracy to synovial fluid white blood cell count and polymorphonuclear percentage for periprosthetic joint infection diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…5 Moreover, adverse events had been reported with medical devices across several specialties, including pelvic floor mesh repair in gynaecology, prosthetic implants in breast surgery, and metalon-metal hip components in orthopaedics. [6][7][8][9][10][11][12] After a transition period of four years, including a one-year postponement due to the COVID-19 pandemic, the EUMDR became fully binding and applicable in May 2021. This article discusses the pertinent points of the EUMDR in relation to orthopaedic medical devices, and explores how this new regulation affects patient safety, technological advances, and future innovation capacity in orthopaedics.…”
Section: The Impact Of the European Union's Medical Device Regulation...mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Moreover, adverse events had been reported with medical devices across several specialties, including pelvic floor mesh repair in gynaecology, prosthetic implants in breast surgery, and metalon-metal hip components in orthopaedics. [6][7][8][9][10][11][12] After a transition period of four years, including a one-year postponement due to the COVID-19 pandemic, the EUMDR became fully binding and applicable in May 2021. This article discusses the pertinent points of the EUMDR in relation to orthopaedic medical devices, and explores how this new regulation affects patient safety, technological advances, and future innovation capacity in orthopaedics.…”
Section: The Impact Of the European Union's Medical Device Regulation...mentioning
confidence: 99%
“…14,15 Some scholars have reported that this will improve patient safety and ensure that new medical devices are only implanted after their risk profiles have been fully established. 10 However, some companies fear that the more stringent safety and performance requirements will lead to fewer orthopaedic implants being introduced, as additional costs related to administration, legal representation, and research trials to ensure full compliance with these guidelines will eventually lead to higher implant costs. [16][17][18] For existing implants, the EUMDR requires manufacturers to provide a clinical evaluation report to prove their safety and performance.…”
Section: The Impact Of the European Union's Medical Device Regulation...mentioning
confidence: 99%